Inequality in the Representation of Local and Foreign Cuisine in Bali’s Tourism: A Case Study of Pererenan Badung - Putu Gede Wirananda Manggala Putra (UHN IGB Sugriwa Denpasar, 2026)
This study examines theThis study examines the inequality in the representation of local and foreign culinary practices within Bali’s tourism landscape, focusing on Pererenan Village in Badung Regency. Although Bali has formally committed to cultural-based tourism through Governor Regulation No. 5 of 2020 and Governor Regulation No. 99 of 2018, the integration of Balinese cuisine into tourism experiences remains limited. Using a qualitative descriptive design supported by field observations and netnographic analysis, this research explored restaurant characteristics, menu structures, and visual representations across digital platforms such as Google Maps, TripAdvisor, and Instagram. The findings show that restaurants emphasizing Western, Mediterranean, or fusion concepts dominate the area, while traditional Balinese culinary expressions occupy a marginal position. This situation reveals a symbolic contradiction between Bali’s cultural identity and its tourism economy, where global consumption preferences often outweigh local authenticity. The study concludes that strengthening Balinese culinary identity requires more than the use of local ingredients; it demands cultural narrative development, aesthetic representation, and policy support. Collaboration between government institutions, local entrepreneurs, and cultural actors is essential to ensure that Balinese culinary heritage is sustainably preserved and strategically positioned within the evolving tourism industry. inequality in the representation of local and foreign culinary practices within Bali’s tourism landscape, focusing on Pererenan Village in Badung Regency. Although Bali has formally committed to cultural-based tourism through Governor Regulation No. 5 of 2020 and Governor Regulation No. 99 of 2018, the integration of Balinese cuisine into tourism experiences remains limited. Using a qualitative descriptive design supported by field observations and netnographic analysis, this research explored restaurant characteristics, menu structures, and visual representations across digital platforms such as Google Maps, TripAdvisor, and Instagram. The findings show that restaurants emphasizing Western, Mediterranean, or fusion concepts dominate the area, while traditional Balinese culinary expressions occupy a marginal position. This situation reveals a symbolic contradiction between Bali’s cultural identity and its tourism economy, where global consumption preferences often outweigh local authenticity. The study concludes that strengthening Balinese culinary identity requires more than the use of local ingredients; it demands cultural narrative development, aesthetic representation, and policy support. Collaboration between government institutions, local entrepreneurs, and cultural actors is essential to ensure that Balinese culinary heritage is sustainably preserved and strategically positioned within the evolving tourism industry.